The phenomenon and suppression strategy of overvoltage caused by PV power reverse flow - Xie, Yumeng; Li, Qiying; Yang, Lei; Yang, Kun; Wang, Zhen; Liu, Jie; Fan, Hongjin (Frontiers in Energy Research, 2024)
In the current distribution network's energy structure, photovoltaic (PV) occupies a high proportion. However, the access of a high proportion of PV will lead to the phenomenon of reverse power flow in the distribution network, and then the problem of line overvoltage. When the reverse power flow increases, the problem of line overvoltage also worsens, which endangers the normal operation of power system. To solve this problem, this paper starts with the voltage rise theory of distribution network lines. Firstly, through strict mathematical derivation, it compares the influence of main network line parameters and distribution network line parameters on the voltage rise, and summarizes a simple calculation equation for the voltage rise of the distribution network with high proportion PV. Then, according to the mechanism of voltage rise and the principle of inverter control, considering the economy and practicability of the overvoltage suppression strategy, a reverse power flow overvoltage suppression strategy of a system with high proportion PV is proposed. Finally, a PV system model simulating a small village is used to verify the effectiveness of the proposed overvoltage suppression strategy.